Legal Aspects of Telepathology - Christian Dierks (Analytical Cellular Pathology)
In some legal surroundings telepathology is considered a breach of registrational barriers. The recommendation of the G 8 states in Europe for required legislation in telemedicine suggests to recognise that the localization of the remote health care professional defines the site not only of licensure but also of liability. This approach must be considered helpful, since it can solve many problems brought about by the doubtful results of private international law and conventions like the European Union (EU) and Lugano Convention. Under today's conditions in private international law it must be considered essential to agree upon a choice of law and stipulate a court of jurisdiction when doing telepathology. However, the opposing aims of insuring the patients claims and avoiding jurisdictions that exceed the local expectations of the medical professional must be reconciled. Data protection and data security are other crucial topics that require attention. Generally speaking, the principles of minimum data exchange, anonymity, pseudonymity and cryptography must be established as a basis for all telepathology procedures. Only when personal data is needed, its use can be legitimated. Written consent of the patient is advised. To guarantee a cross‐border security level the regulations of the EU‐Data Protection Directive need to be transformed into national law. In practise, cross‐border dataflow shall only take place where the security level can be maintained even within the other country. Finally, reimbursement questions must be answered to establish a sound economical basis for telepathology. The spatial distance between the participants may yield the question, whether the service has been rendered to an extent necessary and sufficient for reimbursement. If reimbursement takes place on a cross‐border or cross‐regional level, severe disturbances of the health systems can occur. Regulation schemes or treaties need therefore to be developed to avoid such disturbances and encompass mutual standards of care as well as methods to balance reimbursement.